2015
DOI: 10.1002/adfm.201500110
|View full text |Cite
|
Sign up to set email alerts
|

Soft, Flexible Freestanding Neural Stimulation and Recording Electrodes Fabricated from Reduced Graphene Oxide

Abstract: . (2015). Soft, flexible freestanding neural stimulation and recording electrodes fabricated from reduced graphene oxide. Advanced Functional Materials, 25 (23), 3551-3559. Soft, flexible freestanding neural stimulation and recording electrodes fabricated from reduced graphene oxide AbstractThere is an urgent need for conductive neural interfacing materials that exhibit mechanically compliant properties, while also retaining high strength and durability under physiological conditions. Currently, implantable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
148
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 65 publications
4
148
0
1
Order By: Relevance
“…[ 1 ] Graphene extends to various fi elds including catalysts, [ 2 ] conductive substrates, [ 3 ] water treatment, [ 4 ] and electrode materials for energy storage devices. [ 5 ] Nevertheless, having been shown that graphene has a profound impact in many areas, it should be noted that improving the thermal stability of graphene still represents a challenge which will greatly restrict the fi eld of application in various aspects due to its low decomposition temperature (below 600 °C in air).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Graphene extends to various fi elds including catalysts, [ 2 ] conductive substrates, [ 3 ] water treatment, [ 4 ] and electrode materials for energy storage devices. [ 5 ] Nevertheless, having been shown that graphene has a profound impact in many areas, it should be noted that improving the thermal stability of graphene still represents a challenge which will greatly restrict the fi eld of application in various aspects due to its low decomposition temperature (below 600 °C in air).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen can serve as foaming agent and produce large volumes of noncombustible gases such as N 2 , NH 3 , and N x O y when burning. [ 10 ] On the other hand, the addition of phosphorus is to form, during the combustion, an impermeable, semisolid, and vitreous layer essentially composed of polyphosphoric acid and to activate the process of formation of intumescence.…”
mentioning
confidence: 99%
“…Other coatings, including polymer coatings such as poly‐3,4‐ethylenedioxythiophene (PEDOT) doped with para ‐toluene sulfonate (pTS), have demonstrated superior signal‐to‐noise ratios and biostability compared to other doped conducting polymers or bare iridium electrodes. Furthermore, new electrodes, such as those made from liquid dispersions of graphene oxide or platinum‐elastomer composites, are mechanically more pliable then crystalline silicon or noble metal electrodes, and have been shown to reduce glial scarring and eventual electrode loss of function . These efforts are ongoing, and may yield significant improvements in the biostability and electrical properties of neuroprosthetics.…”
Section: Introductionmentioning
confidence: 99%
“…These flexible organic and hybrid electrodes can be introduced deep in the brain through releasable injection microneedles [122] or capillary syringe needles [123], can be stereotaxically implanted after rapid freezing in liquid nitrogen [124] or by coating the electrodes with a rigid and dissolvable sucrose carrier needle [121] (Figure 9b). Such techniques allow the insertion of flexible probes able to perform deep brain stimulations by reducing the risk of tissues damaging after the implant due to motions of the implant itself.…”
Section: Flexible Microelectrodesmentioning
confidence: 99%